Bifunctional poly(ionic liquid) catalyst with dual-active-center for CO2 conversion: Synergistic effect of triazine and imidazolium motifs. Issue 54 (December 2021) - Fang, Xu; Liu, Chengcheng; Yang, Li; Yu, Tie; Zhai, Dong; Zhao, Wenling; Deng, Wei-qiao
Graphical abstract: Here we report a bifunctional poly(ionic liquid) heterogeneous catalyst with dual-active-center for enhanced CO2 conversion, in which the triazine and imidazolium motifs play synergistic roles for CO2 conversion. Highlights: A triazine-functionalized poly(ionic liquid) (T-PIL) was designed and synthesized. This metal free T-PIL was an efficient catalyst for the CO2 cycloaddition without co-catalysts. The yields of the target products were improved up to three times in the presence of triazine motifs. Intramolecular synergistic mechanism was proposed based on DFT calculations and in-situ DRIFTS. Abstract: Developing heterogeneous catalyst containing both CO2 -philic groups and catalytic active sites is highly desirable for efficient CO2 chemical fixation. In this work, a triazine-functionalized poly(ionic liquid) (T-PIL) was designed and synthesized. This metal free catalyst showed extremely enhanced CO2 adsorption and improved catalytic ability for the cycloaddition reaction of CO2 without co-catalysts. Especially for the epoxides of large size and strong steric hindrance, the yields of the cyclic carbonates were improved up to three times in the presence of triazine motifs. An intramolecular synergistic mechanism of triazine and imidazolium motifs was proposed on the basis of density functional theory (DFT) calculations and diffused reflectance infrared Fourier transform spectroscopy (DRIFTS). The imidazolium groups with paired bromine anions acted as catalytic active sites and would enhance CO2 activation and the ring-opening of epoxides. While the triazine groups acting as CO2 -philic groups could enhance the CO2 adsorption and activation. This work highlights that the incorporation of two motifs with synergistic effect in one catalyst can significantly improve its catalytic performance.